2012
DOI: 10.1371/journal.pone.0038204
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing of Bacterial Symbionts within Axinella corrugata Sponges: Diversity and Seasonal Variability

Abstract: Background Marine sponge species are of significant interest to many scientific fields including marine ecology, conservation biology, genetics, host-microbe symbiosis and pharmacology. One of the most intriguing aspects of the sponge “holobiont” system is the unique physiology, interaction with microbes from the marine environment and the development of a complex commensal microbial community. However, intraspecific variability and temporal stability of sponge-associated bacterial symbionts remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
67
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 64 publications
(94 reference statements)
5
67
2
3
Order By: Relevance
“…HK1, have been reported in taxonomically distant sponges that live at varying latitudes and depths (Taylor et al, 2007b;Jensen et al, 2008;Kennedy et al, 2008;Giles et al, 2012;Radax et al, 2012;KarlinskaBatres and Wörheide, 2013;Pita et al, 2013;Olson et al, 2014;Della Sala et al, 2014). Furthermore, other studies on sponge symbionts have recorded the presence of both known and novel Chromatiales representatives belonging to either the Ectothiorhodospiraceae or Chromatiaceae family (Imhoff and Trüper, 1976;White et al, 2012), as well as sulfur-oxidizing bacteria from the Alphaproteobacteria class (Rhodospirillaceae, Rhodobacteraceae) and the phylum Chlorobi (Imhoff and Trüper, 1976;Bondarev et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…HK1, have been reported in taxonomically distant sponges that live at varying latitudes and depths (Taylor et al, 2007b;Jensen et al, 2008;Kennedy et al, 2008;Giles et al, 2012;Radax et al, 2012;KarlinskaBatres and Wörheide, 2013;Pita et al, 2013;Olson et al, 2014;Della Sala et al, 2014). Furthermore, other studies on sponge symbionts have recorded the presence of both known and novel Chromatiales representatives belonging to either the Ectothiorhodospiraceae or Chromatiaceae family (Imhoff and Trüper, 1976;White et al, 2012), as well as sulfur-oxidizing bacteria from the Alphaproteobacteria class (Rhodospirillaceae, Rhodobacteraceae) and the phylum Chlorobi (Imhoff and Trüper, 1976;Bondarev et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…The general consensus is that sponge-microbe associations are largely stable over temporal scales (56), including epibionts (31), cultivatable symbionts (68), and entire bacterial communities (57,60,61,73). Other studies have reported higher levels of variability across seasons (74) and when repeatedly sampling the same individuals over time (3), indicating some degree of symbiont fluctuation over time and individual variation among hosts.…”
mentioning
confidence: 99%
“…미생물 군집구조의 분석에는 16S rDNA에 기반한 PCR-DGGE (polymerase chain reaction-denaturing gradient gel electrophoresis), T-RFLP (terminal-restriction fragment length polymorphism), pyrosequencing 등 다양한 분자적 방법들이 이용되고 있으며, 배 양(culture-dependent)과 비배양(culture-independent)에 근거하여 군집 분석이 이루어지고 있다 (Jackson et al, 2012;White et al, 2012). 해면 공생미생물은 그 수와 종류에 있어 매우 풍부하고 다양하여 29개의 문에 이른다 (Dupont et al, 2013 …”
unclassified